Housing tenure choices of rural migrants in urban destinations: a case study of Jiangsu Province, China. Issue 3 (3rd April 2017) - Tang, Shuangshuang; Feng, Jianxi; Li, Mingye
Abstract: In China, rural migrants to urban destinations often experience poor living conditions and a low rate of homeownership, which are viewed as the results of urban institutional restrictions. Previous studies have primarily focused on rural migrants' living conditions and comparisons of housing tenure between migrants and local citizens in large, high-level cities. However, the status and determinants of housing tenure choices of rural migrants in urban destinations other than large cities are generally overlooked. Moreover, several factors, such as rural landholding and migrants' intention, are rarely studied. Using data from a 2010 survey conducted in Jiangsu Province, multinomial logistic regression models are adopted to explore the features and determinants of rural migrants' tenure choices in urban destinations. In addition to the urban institutional scheme and housing market, rural land and migrants' intention are found to play important roles in tenure choices of rural migrants in urban destinations.